Doubled Genomes, Divergent Fates: Genomic Insights Into Diversification in an Allotetraploid Cavefish - Santiago Montero‐Mendieta; Yuwei Wang; Chongnv Wang; Fanwei Meng; Yahui Zhao; Xinxin Li; Baocheng Guo (Molecular Ecology, 2025)
Cave environments impose unique challenges that drive remarkable genetic and phenotypic changes in cave‐dwelling organisms. In this study, we investigated the genomic basis of adaptation in the small eye golden‐line fish ( Sinocyclocheilus microphthalmus ), an allotetraploid cavefish endemic to Guangxi, China. Using whole‐genome resequencing data from 47 individuals across six cave locations, we examined how neutral and selective forces influence diversification. Our analyses uncovered significant population structure indicative of allopatric divergence, along with evidence of locus‐specific selection contributing to genomic differentiation. We identified seven single outlier clusters (SOCs), each tied to the divergence of specific populations, underscoring the role of local processes in driving diversity. Genes associated with vision showed relaxed selection, likely reflecting adaptation to darkness, while positive selection on other loci revealed additional functional shifts. Notably, allopolyploidy was found to fuel divergence through subgenome‐specific patterns and asymmetric evolution within SOCs and among homoeologs. Taken together, these findings provide valuable insights into mechanisms of cave evolution and illustrate how allotetraploid genomes can facilitate diversification, potentially contributing to speciation in extreme environments.